Performance and Surface Integrity of Nimonic75 Alloy Machined by Electrical Discharge Machining. (2015) - Choudhary, Rajesh; Gupta, Vivek Kumar; Batra, Yogesh; Singh, Akashdeep
Abstract: The ongoing developments in the field of materials science have developed many high strength and temperature resistant (HSTR) metal alloys that are difficult to machine by the conventional machining. Electrical discharge machining is one of the commonly used non-conventional machining processes used to machine hardened tool steels and conductive advanced materials. In this study effect of machining parameters like tool polarity, current, pulse on-time and voltage has been investigated on surface roughness of Nimonic 75 alloy using Taguchi's experimental design technique. From the S/N ratio plots It was observed that tool polarity, pulse on-time and current are most influential parameter that affect surface roughness in EDM. The surface machined by the negative tool polarity was found to be smoother than the positive tool polarity. The deposition rate of the negative polarity tool electrode was comparatively more than the positive polarity tool electrode. The maximum deposition of carbon was observed on the surface machined with positive polarity tool electrode.